Analysis of the Influence of Diamond Fraud, Integrity, and Religiosity on Academic Fraud Behavior - Widyana Anjani; Winarsih Winarsih (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2024)
This study aims to determine the effect of pressure, opportunity, rationalization, capability, integrity, and religiosity on academic cheating behaviour in undergraduate accounting students from Islamic-based universities in Semarang. This research is included in the comparative causal research. The population of this study was undergraduate accounting students from Islamic-based universities in the city of Semarang, namely Universitas Islam Sultan Agung, Muhammadiyah University, Wahid Hasyim University, and UIN Walisongo Semarang. The sampling technique used was purposive sampling. The sample used in this study was 60 students. The data analysis techniques used are descriptive statistics, data quality test, classical assumption test, multiple linear regression analysis, model goodness test, and individual parameter significance test. Pressure has been proven to positively and significantly affect the academic cheating behaviour of accounting students from Islamic-based universities in Semarang. Pressure is proven to have a positive and significant effect. Opportunity is proven to have a positive and significant effect. Rationalization is proven to have a positive and significant effect. Ability is not proven to have a significant effect. Integrity has yet to be proven to have a significant effect. This means that high integrity does not influence students to suppress academic cheating behaviour. Religiosity has not been proven to significantly affect the academic cheating behaviour of accounting students at Islamic-based colleges in Semarang City. This means that high religiosity does not influence students to suppress academic cheating behaviour.